The SHIFT study: exploring the role of a baby-led feeding approach on infant growth - implications for childhood obesity - Sara Jones (2020)
Recently, a baby-led weaning method of complementary feeding, where infants are allowed to self-feed whole foods has grown in popularity. Proponents of the method posit that it may reduce risk of overweight because the self-feeding aspect (and the lower level of maternal control that this affords) is likely to allow infants to better regulate their appetite, and this has been supported by exploratory research (Brown & Lee, 2011b; Brown & Lee, 2012). However, the impact of the method on infant growth has been largely untested, with studies focusing on the potential effects of baby-led weaning on later overweight (Townsend & Pitchford, 2012; Brown & Lee, 2015). Furthermore, studies focus on the self-feeding aspect of the baby-led weaning method, and do not consider the impact of, and the interaction with other feeding behaviours. The SHIFT (Studying Healthy Infant Feeding and growth Trajectories) study explored associations between aspects of infant feeding; milk-feeding, the age of introduction to complementary foods, the transition from milk onto foods, the method of introduction to food (self-feeding or spoon-fed), diet and texture offered, and growth outcomes of infants aged 6-12 months. This research did not find a conclusive association between the baby-led weaning method (i.e. self-feeding) and infant growth. However, behaviours which could be considered to be more broadly ‘baby-led’ in approach; breastfeeding, later age of introduction to complementary foods and a gradual transition from milk onto a diet consisting of mainly whole foods, appeared to foster healthier weight gain trajectories. These findings support the WHO (2003b) recommendation for ‘responsive’ infant feeding. Why mothers choose a more baby-led or parent-led approach is complex; concerns around infant weight, intake and behaviour are commonly cited as driving parent-led behaviour (Redsell et al., 2010; Clayton et al., 2013; Brown & Harries, 2015), and were also reported by mothers in this study. The SHIFT study provides the impetus for effective support for parents in infant feeding, so that they feel confident adopting a baby-led, responsive approach.